Nonsurgical embryo recovery and transfer in sheep and goats - Fonseca, Jeferson F.; Souza-Fabjan, Joanna Maria G.; Oliveira, Maria Emilia F. [UNESP]; Leite, Ceci R.; Nascimento-Penido, Paula Maria P.; Brandao, Felipe Z.; Lehloenya, Khoboso C. (Elsevier B.V., 2016)
The embryo transfer techniques used in small ruminants worldwide are based in surgical procedures. These actions are performed under general anesthesia which needs a combination of animal fasting and drugs for secure animal handling and surgery manipulations. Therefore, it involves risks to animal health and life. The major limiting sequels are adhesions formed by the abdominal surgery, in the ovaries, uterus, or between them. These occurrences can both compromise uterus accessing and oocyte capture and are responsible for decreasing success and limiting successive embryo collections. In contrast, nonsurgical embryo procedures can be performed in a relatively simplified way. Nonsurgical embryo recovery does not need animal prolonged starvation, drug retention is minimized, and donors can stay in a standing position. After the end of embryo recovery, donors are promptly restored to their routine housing and feeding. Furthermore, this technique does not need incisions and, therefore, can be used repetitively in superovulated or nonsuperovulated goats and sheep for embryo recovery a similar procedure done in cattle. In Brazil, promising results are reported using nonsurgical embryo transfer in recipient goats, and studies are currently evaluating similar procedures in sheep. Therefore, this review aimed to present the current panorama of nonsurgical embryo transfer in sheep and goats. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Cervical dilation; Small ruminants; Transcervical embryo collection